Internalization of Islamic Education Values in a Cultural Frame: A Systematic Literature Review in Wayang Art - Sari, Nur Indah; Asy'arie, Bima Fandi; Jamilah; Fitriyah; Ridho, Miftahur (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research aims to identify types of wayang and analyze the values ​​of Islamic education contained in it. This research used a Systematic Literature Review (SLR) with a qualitative approach. The data were obtained from Google Scholar and ScienceDirect. Then, a bibliometric analysis was performed to understand the bibliographic landscape with VOSviever. To gain credibility of the data as the main findings of 24 article documents, Publish or Perish was used. The Nvivo application was also used to guarantee the validity of the data as the data was obtained. The findings revealed that first, the types of wayang played by puppeteers and stories (characters) that have elements of Islamic education, including (1) Wayang Beber, (2) Wayang Orang, (3) Wayang Golek, (4) Wayang Purwa, (5) Wayang Menak, (6) Wayang Syadat, (7) Wayang Sukuraga, (8) Wayang Gung, (9) Wayang Tavip. Second, some of the values ​​of Islamic education contained in wayang art are strengthening the identity of Islamic values, integrating culture and religion, strengthening character education, providing an effective medium for preaching, and providing interactive and reflective learning. Thus, the internalization of Islamic education in wayang art has a relationship that combines religious values ​​and local culture.